(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Nowadays, several businesses are introducing new product lines or services, but are not correctly allocating their efforts to reach their target segments. Businesses are spending a lot of money on awareness through different platforms, but are they reaching the right segment? This case tackles a prominent issue that many businesses face today. GDS Xerox is a Xerox concessionaire company that does the following activities: selling printing machines and equipment, offering maintenance services, and has its own business centers offering printing services. The company recently introduced a new service in its business centers, which is selling customized giveaways (including mugs, coasters, etc.). GDS Xerox is indecisive about what efforts should it should allocate to increase sales revenue in the business services activity after introducing new services. The company is unsure which segment it is targeting with these new services. This leads to allocating marketing activities that target several segments without focusing on a specific segment to reach. Is it targeting companies or individuals? This also leads to a minimal increase in sales revenue, and low awareness as the target segment has not been decided yet. The idea of segmentation is crucial because companies have a certain budget to spend on marketing, and indecisiveness about the target audience might prevent the company from reaching its target audience. Therefore, the company might not be able to achieve its objectives